Response of wheat (Triticum aestivum) genotypes under varying fertility levels in alpine climate of lahaul valley in western Himalaya - Meena, Raj Pal; Chander, Subhash; Chhokar, RS (Journal of Cereal Research, 2011)
A field experiment was conducted at Research Farm of Directorate of Wheat Research, Regional Station, Dalang Maidan (Wheat Summer Nursery) Lahaul & Spiti, Himachal Pradesh during the summer seasons (May to October) of year 2009 and 2010 to identify the most suitable genotypes for cultivation in alpine climate of Western Himalyas with two levels of fertility and seventeen wheat genotypes in a split plot design. Application of recommended dose of fertilizers (RDF) recorded significantly higher values of yield attributes and yield compared to application of half dose of the recommended fertilizers. Wheat genotype ‘HPW 89’ was superior to other 16 genotypes with significantly high grain yield 47.17 and 45.87 q/ha during the year 2009 and 2010 respectively, at recommended dose whereas 31.60 & 31.73 q/ha in the first and the second year respectively at half of the recommended dose. The other superior genotypes were ‘VL 892’, ‘HPW 251’, ‘VL 829’ under RDF and ‘HS 295’, ‘HPW 211’, ‘HPW 236’ under half of the RDF.